Influence of the climate on productivity and the eucalyptus drought response and a proposal for maximizing wood productivity in function of soil attributes in Brazil - Silva, Vinicius Evangelista [UNESP]; Buzzetti, Salatier [UNESP]; Montanari, Rafael [UNESP]; Panosso, Alan Rodrigo [UNESP]; Moreira, Sharlles Christian Dias; Silva, João Flávio da (Universidade Federal de Santa Maria, 2022)
The genetic gains from eucalyptus breeding programs have decreased, compared to the previous decades, while the productivity has declined in recent years. This drop is mainly attributed to climate change, which, according to studies, has limited the productivity and altered the adaptation of forest species. In addition to this, it is considered that the soil is one of the components of the forest production that acts directly on the dynamics of water and nutrients for trees, and it is intended to evaluate the attributes of soils that maximize the productivity of wood to assist forestry companies in the indication of soils with better productive capacity to produce wood. Thus, the aim of the present study was to evaluate the influence of climate and soil attributes on the productivity of the eucalyptus forest and on the response to drought in Brazil (tropical and subtropical) in places with three types of climate: sub-humid, humid and super-humid. In addition, we sought to calculate a proposal for optimal values of stable soil attributes over a forest cycle/rotation to maximize Eucalyptus productivity. To do so, 24 experiments were installed in Brazil with 4 common clones in all the experiments to obtain strong edaphoclimatic contrasts, and, thus, to measure the productivity and the response to drought and to describe its relationship with the attributes of the soils. Three climatic groups were evaluated: Sub-humid (precipitation rate: evapotranspiration between 0.5 to 1.0, Wet (precipitation rate: evapotranspiration between 1.0 to 2.5), Super-humid (precipitation rate: evapotranspiration between 2.5 to 5.0). Wood productivity varied among Eucalyptus clones, with an average of 1.86 being the variation range. The genotype versus environment interaction (G X E) was strongly noted, and it was observed that some clones are more affected by the climate in relation to others. The optimal values of Sand, Clay, Silt, CEC, O.M to maximize the wood productivity were: 54.68 %, 18.94 %, 7.02 %, 31.49 mmolc/dm³, 27.17 g/cm³.
Influência do clima na produtividade e resposta à seca do eucalipto e uma proposta de maximização da produtividade de madeira em função dos atributos do solo no Brasil
Keywords: Climate; Edaphoclimatic groups; Soil quality; Tolerance to forest aridity